Pursuing Women's Economic Empowerment. (Policy Papers; Policy Paper ;, 2018)
The economic and social imperative for women's economic empowerment is clear. Greater gender equality boosts economic growth and leads to better development outcomes. It contributes to reducing income inequality and boosting economic diversification and, in turn, supports economic resilience. Gender equality is one of the 17 global UN Sustainable Development Goals, which provide a roadmap for ending poverty, protecting the planet, and ensuring that all people enjoy peace and prosperity. The G7 has emphasized the need for closing the gender gap. The Taormina Leaders' Summit in 2017 renewed the emphasis on promoting women's empowerment, which the leaders see as a crucial contribution to promoting sustainable development. In this regard, leaders committed to mainstreaming gender equality into all their policies. This is carried forward by Canada's G7 Presidency. With growing recognition that gender equality promotes economic stability and growth, the IMF has scaled up its work in this area and is committed to continue these efforts. Work by the IMF will focus on (i) deepening its understanding of the economic benefits of women's empowerment, both in the labor market and through more equal opportunities for boys and girls, also against the background of persistent megatrends, including in an environment of rapid technological change; (ii) integrating the analysis into Fund policy dialogue with member countries; (iii) providing customized assistance, workshops, and peer-learning courses in areas such as gender budgeting; and (iv) expanding collaboration with other international institutions on the subject to benefit from complementary areas of expertise.